PENDIDIKAN KARAKTER DALAM PERSPEKTIF TUAN GURU BESILAM LANGKAT (Studi Interpretative Phenomenologi Tarekat Naqsyabandiyah Babussalam) - Syukri, Ahmad; Mardianto, Mardianto; Mahariah, Mahariah (JURNAL TARBIYAH, 2024)
This research discusses Character Education from the Perspective of Tuan Guru Besilam Langkat (Interpretive Phenomenological Study of the Naqsyabandiyah Babussalam Tarekat). The problems discussed in this research are seen from a very urgent phenomenon among society, namely character education. This research aims to find out what the views of Tuan Guru Belilam Langkat are and the wisdom implemented in the Naqsyabandiyah Babussalam Tarekat concept in implementing character education. Therefore, the author wants to conduct this research using a qualitative type of research with a Phenomenological study. The data obtained is based on observations, interviews and documentation studies. The analysis technique uses methods; data reduction, data presentation, conclusions. Then check the validity of the data by; credibility test, transferability test, defendability test, confirmability test.